Development of higher order thinking skill test instrument in packaged foods topic to enhance critical thinking ability of junior high school students - Destriyanti Fikri Fadillah; Dwi Indah Suryani; Annisa Novianti Taufik (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Schools have not fully implemented learning activities designed to improve students' critical thinking skills. The HOTS test instrument can teach students to think critically. This research aims to analyze the level of validation of the HOTS test instrument on the theme of packaged food to foster the critical thinking skills of junior high school students. This study uses the Borg & Gall development model as a research and development (R&D) method. The R&D stages include potential and problem analysis, data collection, product design, validation, and revision. This research results from the HOTS test instrument, which consists of 30 open essay questions. The validation results show that, based on material experts, 82.8% are included in the valid category, 92.3% are included in the very valid category based on evaluation experts, and 87.82% are included in the very valid category based on expert practitioners. The HOTS test instrument on packaged food to foster critical thinking skills of junior high school students is very valid (87.64%) overall.